2011
DOI: 10.1682/jrrd.2010.08.0149
|View full text |Cite
|
Sign up to set email alerts
|

Target Achievement Control Test: Evaluating real-time myoelectric pattern-recognition control of multifunctional upper-limb prostheses

Abstract: Abstract-Despite high classification accuracies (~95%) of myoelectric control systems based on pattern recognition, how well offline measures translate to real-time closed-loop control is unclear. Recently, a real-time virtual test analyzed how well subjects completed arm motions using a multiple-degree of freedom (DOF) classifier. Although this test provided real-time performance metrics, the required task was oversimplified: motion speeds were normalized and unintended movements were ignored. We included the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
193
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(197 citation statements)
references
References 24 publications
4
193
0
Order By: Relevance
“…the average completion time was 2.9 seconds with a standard deviation of 3.57 seconds, as compared to the results of the virtual arm model, i.e. 5.95 seconds and 3.57 seconds, respectively [16].…”
Section: Mean Average Time To Target and Standard Deviation Time To Tmentioning
confidence: 73%
See 3 more Smart Citations
“…the average completion time was 2.9 seconds with a standard deviation of 3.57 seconds, as compared to the results of the virtual arm model, i.e. 5.95 seconds and 3.57 seconds, respectively [16].…”
Section: Mean Average Time To Target and Standard Deviation Time To Tmentioning
confidence: 73%
“…The results showed that the velocities forecasted by the decoders were sent as kinematic control signals to the robot at a rate of 60 Hz, ultimately showing that less time is required for the completion of movement [15]. Similarly, Simon et al [16] obtained the average completion rate to show the time taken by the cursor to reach the target and complete the task. They set completion time as "the time from trial start to the successful achievement of the target posture, not including the 2 seconds dwell" [16].…”
Section: Mean Average Time To Target and Standard Deviation Time To Tmentioning
confidence: 95%
See 2 more Smart Citations
“…Although the blind irritants in the treatment of the external space information are not done directly by the visual cortex, yet it is completed by hearing and touch. But looking at clinical trials, the blind of the visual cortex can be activated and reused in order to help the blind perceive the world better, which provides the reason for the basic theoretical basis of this paper [1].…”
Section: Introductionmentioning
confidence: 99%